Does the impact of biodiversity differ between emerging and endemic pathogens? The need to separate the concepts of hazard and risk. (24th April 2017) - Hosseini, Parviez R.; Mills, James N.; Prieur-Richard, Anne-Hélène; Ezenwa, Vanessa O.; Bailly, Xavier; Rizzoli, Annapaola; Suzán, Gerardo; Vittecoq, Marion; García-Peña, Gabriel E.; Daszak, Peter; Guégan, Jean-François; Roche, Benjamin
Abstract : Biodiversity is of critical value to human societies, but recent evidence that biodiversity may mitigate infectious-disease risk has sparked controversy among researchers. The majority of work on this topic has focused on direct assessments of the relationship between biodiversity and endemic-pathogen prevalence, without disentangling intervening mechanisms; thus study outcomes often differ, fuelling more debate. Here, we suggest two critical changes to the approach researchers take to understanding relationships between infectious disease, both endemic and emerging, and biodiversity that may help clarify sources of controversy. First, the distinct concepts of hazards versus risks need to be separated to determine how biodiversity and its drivers may act differently on each. This distinction is particularly important since it illustrates that disease emergence drivers in humans could be quite different to the general relationship between biodiversity and transmission of endemic pathogens. Second, the interactive relationship among biodiversity, anthropogenic change and zoonotic disease risk, including both direct and indirect effects, needs to be recognized and accounted for. By carefully disentangling these interactions between humans' activities and pathogen circulation in wildlife, we suggest that conservation efforts could mitigate disease risks and hazards in novel ways that complement more typical disease control efforts. This article is part of the themed issue 'Conservation, biodiversity and infectious disease: scientific evidence and policy implications'.